Верхньопалеолітична стоянка Пушкарі ІІІ - Васильєв, П.М.; Дудник, Д.В. (Археологія і давня історія України, 2019)
Вводиться до наукового обігу крем'яна колекція зі стоянки Пушкарі ІІІ, що походить з поверхневих
зборів. Отриманий матеріал має низку характерних особливостей, які відрізняють його від відомих комплексів Пушкарі І і Погон. This article deals with new flint collection (surface
materials) from Upper Paleolithic site Pushkari III near v. Pushkari Novgorod-Siversky district of the
Chernihiv region. Site is located on the high right bank of the Desna River, and occupies the southwestern part
of the Cape of Pogon. The flint collection of artifacts is 910 items, more
of them are flakes, blades, cores, chunks and chips. In addition, 107 tools were found, of theme: retouched
blades and flakes, burins, end scrapers, combined tools (end scraper / burin). A non-numerical microlithic complex
amounting to only 6 units proved to be rather informative and atypical. It consists of one rectangle,
three medial fragments and two proximal fragments, probably points. The presence of a microlith complex
in a pivotal, in one case practically vertical, dulling retouch contrasts sharply with the microlithic products
of Pushkar I and Pogon. And in combination with ventral thawing on one of the products, an analogy with
the points of the Molodovo 5 layer 7. For a more detailed analysis, the determination of
the place and role of the above-described material in understanding the problem of the dynamics of the settlement
of Pogonese capes before and after LGM requires archaeological research.